(untitled) (Eurasian Journal of Philology Science and Education, 2016)
In the article the notion of «philosophic prose» as a special genre of literature is elaborated. The article shows that though Prishvin had not written a single purely philosophic treatise, his Diary and his fiction are satiated with meditation on really philosophic questions – these are the themes of historiosophy, anthropology, ethics and aesthetics, ecological problems of the Soviet world system. Examples of the philosophic-world-outlook dialogue of the writer with a number of outstanding native and foreign thinkers are given.